2010
DOI: 10.1007/s12098-010-0278-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Nasal-Tragus Length to Estimate Optimal Endotracheal Tube Depth for Neonates in Taiwan

Abstract: Using the NTL to predict the optimal ETT depth with the formula, NTL plus 1 cm, was clinically practical for newborn infants in Taiwan weighing ≤ 2,500 g, and a modified formula, NTL plus 0.5 cm, was more suitable for neonates weighing >2,500 g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Other methods are based on physical markers like NTL, sternal length or head circumference. These may be faster and more accurate to assess the depth of ETT in neonates (9,22). Because the malposition of the ETT can cause serious complications, the rapid determination of tube placement is a very important goal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods are based on physical markers like NTL, sternal length or head circumference. These may be faster and more accurate to assess the depth of ETT in neonates (9,22). Because the malposition of the ETT can cause serious complications, the rapid determination of tube placement is a very important goal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a number of rapid point-of-care methods (e.g., clinical signs, exhaled carbon dioxide (CO 2 ) detectors, respiratory function monitors and ultrasound) to confirm the correct tube placement have been developed (3). Nasal-tragus length (NTL) to predict the optimal ETT depth with the formula, NTL plus 1 cm, has been suggested as clinically practical for newborn infants (9). In our country, NTL is currently used under the Neonatal Resuscitation Program (NRP) recommendations (10).…”
Section: Introductionmentioning
confidence: 99%
“…Malposition of endotracheal tubes has been reported to occur in up to 50% of intubation episodes. [11][12][13] Historically, endotracheal tube position has been confirmed radiologically. Some previous studies suggested that the first thoracic vertebral body was a better marker on chest roentgenogram.…”
Section: Introductionmentioning
confidence: 99%
“…The initial clinical assessment of the appropriate intubation depth is to auscultate equal air-entry to the bilateral lungs. 10,12 Nevertheless, it lacks a quantitative or qualitative change of breathing sound detected on auscultation, despite 1cm downward displacement of the ET tube tip into the main bronchus; one study indicated that up to 60% of endobronchial intubations were by equal breath sound auscultation. 15,21 Thus, several methods have been reported to determine the proper ET tube depth for intubation and the accurate ET tube tip position, such as the well-known 7-8-9 Rule, body parameters as a predictor, the manufacturer's markings on the tube tip and sonogram.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of premature gestation-based recommendations, 4 current age-based formulae have long been recognized as inadequate. Newer weight, 5 length, 6 and anthropomorphic alternatives, such us foot length, 7 middle finger length, 8 and tragus to nares length, 9 have all been studied and found to be better alternatives for infants. Many of these studies were retrospective, and almost all excluded any significant anomalies and pathology.…”
mentioning
confidence: 99%